Healthcare Access and Health-Related Cultural Norms in a Community Sample of Black and Latinx Sexual Minority Gender Expansive Women. Issue 5 (16th April 2023) - Cerezo, Alison; Ching, Sesame; Ramirez, Amaranta
ABSTRACT: Major strides have been made in understanding the impact of intersectionality in everyday life. However, there is a significant gap in the research literature on how individuals with multiple minority statuses must uniquely interact and navigate health services. We carried out an exploratory qualitative study with twenty sexual minority gender expansive women of Latinx and African American descent to explore participants' access to health services and the impact of cultural factors on their health decisions and behaviors. Participants described long-term challenges with accessing health services that were primarily tied to income and discriminatory treatment on the part of health providers. Participants also shared regular discouragement from family members to engage with U.S./Western medicine and health traditions. Together, participants' early life experiences and the continued messages from family members, influenced their health behaviors (e.g., delaying care). Implications for future research and health services are discussed.